Effect of Chitosan Pre-Treatment on Color Fastness of Cotton Fabric with Natural Dyes from Mango Leaves Extract - Febri Fajri Yanti; Namira Rezqia Andevita; Ifa Puspasari (Faculty of Industrial Technology Universitas Islam Indonesia, 2021)
Application of natural dyes in textile coloring has been widely used because it is more environmentally friendly than synthetic dyes and is able to produce various colors from one natural dye. In this study, cotton fabric was treated with chitosan at different concentrations (0, 0.25%, 0.5%, and 1%) to determine its effect on the color fastness using mango leaves extract as natural dyes. Fastness to ironing, washing and sun drying of chitosan-treated samples were measured and compared with untreated samples. The effect of using different types of mordants (ferrous sulphate and alum) was also investigated. Coloring of the dyed fabric was evaluated in terms of color parameters (L* a* b*) and the dye absorption was evaluated using K/S values. The results showed that the color fastness to wet and dry rubbing at each concentrations of chitosan and different types of mordants were good. However, the fabric processed with ferrous sulphate has a lower value of color fastness to ironing than that with alum. The color fastness to washing showed quite good results. The color fastness to sun drying showed that the cotton fabric with or without pre-treatment with chitosan showed good results. However, the value of fabric processed with ferrous sulphate showed very good values compared to alum. High values of K/S were obtained on fabrics pre-treated with chitosan for all types of mordants. Fabric processed with alum showed high color brightness.